Texas High Plains Initiative for Strategic and Innovative Irrigation Management and Conservation. (August 2013) - Weinheimer, Justin; Johnson, Phillip; Mitchell, Donna; Johnson, Jeff; Kellison, Rick
Abstract The strategic management of irrigation applications to improve water‐use efficiency and meet economic objectives has been identified as a key factor in the conservation of water resources in the Texas High Plains region. Two field level demonstration projects have been ongoing in the Texas High Plains to evaluate advantages and disadvantages of irrigation water conservation methods. Since 2010, the North Plains Groundwater Conservation District has evaluated corn production using 12 acre‐inches or less of applied irrigation water with a goal to produce 200 bushels per acre. In the South Plains, the Texas Alliance for Water Conservation (TAWC) has worked directly with 24 producers in Hale and Floyd Counties on 29 sites over the past seven years to monitor water use, soil moisture, crop productivity and economic returns on various cropping systems on over 4, 000 acres. Both of these demonstration projects take an innovative approach to strategic irrigation management that uses new technologies with an overall goal to practice water conservation while maintaining economic profitability.